2021
DOI: 10.1002/cam4.3964
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline in visceral adipose tissue over 1 month is associated with poor prognosis in patients with unresectable pancreatic cancer

Abstract: Background Involuntary weight loss related to cachexia is common in patients with advanced cancer, but the association between body composition changes and survival is still unclear in pancreatic cancer. Methods We retrospectively reviewed the clinical outcomes of 55 patients with advanced pancreatic cancer undergoing palliative therapy or best supportive care (BSC). The skeletal muscle index (SMI), visceral adipose tissue index (VATI), subcutaneous adipose tissue index (SATI), and visceral to subcutaneous adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
4
13
0
Order By: Relevance
“…In our cohort, sarcopenia was observed in 44.2% at the time of diagnosis, which was similar to that of previous reports [7,16]. While some studies suggested association of sarcopenia at diagnosis with prognosis [12,14,25], others reported change in body composition was associated with survival [10][11][12]26]. Sarcopenia before chemotherapy was not associated with PFS or OS in our cohort, by using the criteria developed by the Hepatology Society of Japan based on the AWGS criteria (male SMI < 42 cm 2 /m 2 and female SMI < 38 cm 2 /m 2 ) [23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our cohort, sarcopenia was observed in 44.2% at the time of diagnosis, which was similar to that of previous reports [7,16]. While some studies suggested association of sarcopenia at diagnosis with prognosis [12,14,25], others reported change in body composition was associated with survival [10][11][12]26]. Sarcopenia before chemotherapy was not associated with PFS or OS in our cohort, by using the criteria developed by the Hepatology Society of Japan based on the AWGS criteria (male SMI < 42 cm 2 /m 2 and female SMI < 38 cm 2 /m 2 ) [23].…”
Section: Discussionsupporting
confidence: 91%
“…Cancer cachexia is defined as a multifactorial syndrome defined by an ongoing loss of skeletal muscle mass that cannot be fully reversed by conventional nutritional support and leads to progressive functional impairment [8]. Recent studies suggested that loss of skeletal muscle mass was associated with cancer cachexia, which hindered continuance of chemotherapy, and can be one of prognostic factors of survival in PC [9][10][11][12][13]. However, it remains unclear whether sarcopenia at diagnosis or decline in skeletal muscle mass during chemotherapy is more prognostic of survival in PC, with various regimens such as FOLFIRINOX [14,15] and GnP [16] being evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition, in a retrospective analysis, it was shown that a rapid decline in VAT over 30 days was related with poor outcomes (reduced survival) among patients affected by an unresectable pancreatic cancer. 24 This information highlights the clinical relevance of a short-term assessment of body composition analysis (changes in adiposity) in patients with gastrointestinal cancer that should guide physicians for an early nutritional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical observations indicate that patients with advanced pancreatic cancer lose a large proportion of visceral and subcutaneous adipose tissue rapidly (approximately in 4 weeks), and this was associated with poor survival [37].…”
Section: Discussionmentioning
confidence: 99%